2020
DOI: 10.1177/1350650120965756
|View full text |Cite
|
Sign up to set email alerts
|

The effects of graphene nanoplatelets on the tribological performance of glass fiber-reinforced epoxy composites

Abstract: Over the last decade, FRP composites have seen increased use in many applications, where an optimum combination of light-weight, better wear resistance and excellent mechanical properties have attributed to their uses in different engineering segments. In this study, Mechanical and tribological properties of woven glass fiber-reinforced epoxy (GFRE) composites with and without graphene nanoplatelets (GNPs) were obtained and correlated. The results of the unmodified GFRE laminates (neat GFRE samples) were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…The abrasive wear performance [19,26] of different composites was investigated using a pin-on-disc machine using waterproof SiC (400 grits size) paper from DUCOM, Bangalore, India. A diamond cutter was utilized to cut 10 mm × 10 mm square specimens from composite laminates for wear testing according to the ASTM G99 standard.…”
Section: Abrasive Wear Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The abrasive wear performance [19,26] of different composites was investigated using a pin-on-disc machine using waterproof SiC (400 grits size) paper from DUCOM, Bangalore, India. A diamond cutter was utilized to cut 10 mm × 10 mm square specimens from composite laminates for wear testing according to the ASTM G99 standard.…”
Section: Abrasive Wear Testmentioning
confidence: 99%
“…These studies revealed that functional fillers such as carbon nanofiller and inorganic nanofillers significantly impact wear characteristics. Many different model of wear calculated wear rate as a function of weight percent of filler, mechanical qualities, normal load, etc [25][26][27]. The previous wear models and experimental investigations have one major flaw: they do not account for the impact of specific parameters on composite abrasive wear.…”
Section: Introductionmentioning
confidence: 99%
“…34 This is because the presence of filler particles acted as spacers (surface modifier) which acts as adhesion between the contact surface interface. [39][40][41][42][43][44][45]…”
Section: Coefficient Of Frictionmentioning
confidence: 99%
“…According to these investigations, functional fillers have a considerable impact on wear characteristics. Many various wear models determined wear as a function of filler, average load, and other factors [20][21][22]. The conventional and Taguchi approaches can both be used to look into the impact of specific factors on single response situation optimization.…”
Section: Introductionmentioning
confidence: 99%